2018
DOI: 10.1093/femsle/fny020
|View full text |Cite
|
Sign up to set email alerts
|

Osmotolerance of Dekkera bruxellensis and the role of two Stl glycerol–proton symporters

Abstract: Dekkera bruxellensis is important for lambic beer fermentation but is considered a spoilage yeast in wine fermentation. We compared two D. bruxellensis strains isolated from wine and found that they differ in some basic properties, including osmotolerance. The genomes of both strains contain two highly similar copies of genes encoding putative glycerol-proton symporters from the STL family that are important for yeast osmotolerance. Cloning of the two DbSTL genes and their expression in suitable osmosensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As described by Hohmann (2002) and Zemancíková et al (2018), glycerol proton symporters (Stl1 and Stl2) are important for the osmotic stress resistance of yeasts (e.g., Dekkera bruxellensis and Saccharomyces cerevisiae) through glycerol synthesis and its intracellular accumulation. Most prokaryotic and eukaryotic organisms tolerate hypersaline conditions using an "organic solute-in strategy" through the accumulation of "compatible solutes" (e.g., polyols in fungi) to maintain their intracellular Na + concentrations below the levels that would be toxic for the cells (Hohmann, 2002).…”
Section: Differential Expression Analysismentioning
confidence: 99%
“…As described by Hohmann (2002) and Zemancíková et al (2018), glycerol proton symporters (Stl1 and Stl2) are important for the osmotic stress resistance of yeasts (e.g., Dekkera bruxellensis and Saccharomyces cerevisiae) through glycerol synthesis and its intracellular accumulation. Most prokaryotic and eukaryotic organisms tolerate hypersaline conditions using an "organic solute-in strategy" through the accumulation of "compatible solutes" (e.g., polyols in fungi) to maintain their intracellular Na + concentrations below the levels that would be toxic for the cells (Hohmann, 2002).…”
Section: Differential Expression Analysismentioning
confidence: 99%
“…Analysis of its secondary structure revealed that it is a typical member of the STL family with 12 trans‐membrane segments and conserved motifs typical of this family (Zemancikova et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…(Zemancikova et al . ) was followed. For measuring the intracellular pH, the procedure using cells expressing ratiometric pHluorin described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Bootstrap values below 500 are not shown. The S. cerevisiae glycerol transporter Stl1p and its B. bruxellensis ortholog (Zemancíková et al 2018) were used as outgroups. GenBank protein accession numbers for S. cerevisiae transporters are displayed.…”
Section: Resultsmentioning
confidence: 99%